Tuning the electrocatalysts for oxygen evolution reaction - Eftekhari, Ali (Materials today energy, 2017)
Oxygen evolution reaction (OER) is one of the central reactions in the realm of electrochemistry and has been subject to numerous studies over centuries, but still one of the most complicated electrochemical processes and is of practical importance. It has attracted considerable attention quite recently because of its critical role in various energy storage and conversation systems. However, the quest for finding the most efficient electrocatalysts is still undergoing, and various materials and designs have been recently tested to improve the OER efficiency. By surveying the literature, the present paper concludes that the most reasonable design for the practical development of the OER electrocatalysts is based on a carbon catalyst support and transition metal compounds decorated by metallic catalysts. Based on the available reports, the key features, which are beneficial for improving the OER efficiency, are summarized. Furthermore, since the OER is based on a series of adsorption processes as pseudocapacitance is, it is demonstrated that electrode materials with stronger pseudocapacitive behaviors are more likely to deliver better OER performance. [Display omitted] •Various promising electrocatalysts for OER are investigated.•Different methods for improving the OER electrocatalysis are discussed.•The practical design of the future OER electrocatalysts is introduced based on the available reports.•The relationship of OER electrocatalysis and pre-pseudocapacitance is highlighted.